A qualitative study of community pharmacists' opinions on the provision of osteoporosis disease state management services in Malaysia - Nik, J.; Lai, P.; Ng, C.; Emmerton, Lynne (BioMed Central, 2016)
Background: Osteoporosis has significant impact on healthcare costs and quality of life. Amongst the models for collaborative disease state management services published internationally, there is sparse evidence regarding the role of community pharmacists in the provision of osteoporosis care. Hence, the aim of our study was to explore community pharmacists' opinions (including the barriers and facilitators) and scope of osteoporosis disease state management services by community pharmacists in Malaysia, informing a vision for developing these services. Methods: Semi-structured individual interviews and focus groups discussions were conducted with community pharmacists from October 2013 to July 2014. Three trained researchers interviewed the participants. Interviews were recorded and transcribed verbatim. Data were analyzed thematically using an interpretative description approach. Results: Nineteen community pharmacists with 1-23 years of experience were recruited (in depth interviews: n = 9; focus group discussions: n = 10). These participants reflected on their experience with osteoporosis-related enquiries, which included medication counseling, bone density screening and referral of at-risk patients. Key barriers were the lack of numerous factors: public awareness of osteoporosis, accurate osteoporosis screening tools for community pharmacists, pharmacists' knowledge on osteoporosis disease and medications, time to counsel patients about bone health, collaboration between pharmacists and doctors, and support from the government and professional body. The pharmacists wanted more continuing education on osteoporosis, osteoporosis awareness campaigns, a simple, unbiased osteoporosis education material, and inter-professional collaboration practices with doctors, and pharmacists' reimbursement for osteoporosis care. Conclusions: The involvement of community pharmacists in the provision of osteoporosis disease state management was minimal. Only ad-hoc counseling on osteoporosis prevention was performed by community pharmacists. Development and trial of collaborative osteoporosis disease state management services in community pharmacy could be facilitated by training, support and remuneration.